Human-Building Interaction (HBI) (Occupant comfort and wellbeing, Human-centered IoT design, Adaptive workspaces and behavioral analytics - Salamaga, Diana (Emerging Frontiers Library for The American Journal of Applied Sciences, 2026)
The article offers a comprehensive integrative review of the interdisciplinary field of human–building interaction (HBI), aimed at systematizing its theoretical, technological and applied components. The introduction substantiates the relevance of the topic against the background of the rapid expansion of the intelligent building development segment and identifies a key research gap associated with the fragmentation of existing studies. The purpose of the study is to advance a dynamic process model of HBI by integrating three critical domains: occupant comfort/well-being, human-centered IoT design, and behavioral analytics. Unlike previous static taxonomies, this research posits a causal feedback loop where behavioral analytics serves as the mediating mechanism that translates raw IoT data into adaptive environmental responses, while human-centered design acts as the antecedent condition for user trust. The proposed framework redefines the intelligent building not merely as an automated facility, but as a sociotechnical system dependent on recursive learning between the occupant and the built environment. The study employs a systematic literature review (SLR) methodology following PRISMA guidelines to map the fragmented HBI landscape. The search strategy targeted peer-reviewed articles published between 2015 and 2025 in Scopus, ACM Digital Library, and IEEE Xplore, using the Boolean strings: ("Human-Building Interaction" OR "HBI") AND ("IoT" OR "Ambient Intelligence") AND ("Comfort" OR "Well-being"). Inclusion criteria prioritized studies offering empirical evidence of user-in-the-loop controls and adaptive systems. This academic corpus was triangulated with high-impact industry reports (e.g., Gartner, McKinsey) to ground theoretical models in current market technological capabilities. This dual approach facilitates a valid transition from theoretical synthesis to the proposed conceptual framework. The results obtained encompass: the development of a classification of conceptual HBI models; an analytical assessment of technological solutions for monitoring and maintaining comfort parameters (BEMS, adaptive façades, PCS); a systematization of human-centered design principles for the intelligent environment; as well as an assessment of the impact of adaptive spaces on work performance based on case studies. The conclusion demonstrates that the effectiveness of HBI is determined not by the degree of technological sophistication but by the quality of integration of human-centered principles and by the overcoming of sociotechnical barriers, above all the deficit of trust caused by data privacy risks. The information presented in this study will be of interest to the academic community, architects, engineers and specialists in real estate facility management.